Knoop microhardness of conventional and microwaved denture base acrylic resins - Amanda C Schoeffel; Patricia Bagio; Vinicius T Sakima; Simone Soares; Karin H Neppelenbroek; Vanessa M Urban (Wolters Kluwer Medknow Publications, 2019)
Background: Microwave polymerization reduces the time of acrylic resin processing, but it is important to select a proper cycle to avoid overheating, porosity, and impairment to the materials' properties. Aims: To evaluate the microhardness of conventional (Vipi Cril-VC) and microwaved (Vipi Wave-VW) acrylic resins after microwave polymerization cycles and the cycles recommended by the manufacturer. It was also evaluated the effect of thermocycling on the microhardness of these materials. Methods and Materials: Specimens (n = 10) were made: 1. WB (water-bath recommended for VC polymerization); 2. M630/25 (10 min at 270 W; 5 min at 0 W; 10 min at 360 W: recommended for VW polymerization); 3. M550/3 (3 min at 550 W); and 4. M650/5 (5 min at 650 W). After 48 h in distilled water at 37°C, specimens were subjected to Knoop test under 25 g during 5 s. The same specimens were submitted to thermocycling (5,000 cycles; 5°C and 55°C; 60 s) and the microhardness was again measured. The results were analyzed by repeated measures one-way analysis of variance/Bonferroni for each material (α = 0.05). Results: For both materials, no difference was obtained for groups polymerized using the cycles recommended by the manufacturer (VC = 19.8 ± 0.9 KHN; VW = 21.0 ± 1.6 KHN) and M650/5 (VC = 19.9 ± 1.5 KHN; VW = 20.9 ± 0.8 KHN). After thermocycling, microhardness decreased in experimental cycles for VC (M550/3 = 17.0 ± 1.9 to 14.6 ± 1.2 KHN; M650/5 = 19.9 ± 1.5 to 17.8 ± 0.8 KHN) and in all microwave cycles for VW (M630/25 = 21.0 ± 1.6 to 18.3 ± 0.9 KHN; M550/3 = 17.5 ± 3.0 to 15.7 ± 2.0 KHN; M650/5 = 20.9 ± 0.8 to 18.2 ± 2.0 KHN) (P = 0.000). The lowest hardness was observed for both resins processed by M550/3 (P = 0.001). Conclusions: Both materials could be polymerized in microwave during 5 min showing hardness similar to the cycles recommended by the manufacturer. Thermocycling did not decrease the hardness of VC polymerized with both cycles recommended by the manufacturer and VW polymerized with the water-bath conventional cycle.